Maize population density, light attenuation coefficient and yield - Morales Ruiz, Alejandro; Morales Rosales Edgar Jesús; Franco Mora, Omar; Mariezcurrena Berasaín Dolores; Estrada Campuzano, Gaspar; Norman Mondragón Tomás Héctor (Revista Mexicana de Ciencias Agrícolas, 2018)
During 2008 and 2009 six maize cultivars were evaluated under three population densities in Toluca, Mexico to determine leaf area index, light attenuation coefficient, intercepted radiation, radiation-use efficiency and grain yield. A randomized complete block design in a split- plot arrangement was used, large plots corresponded to the population densities (6.9, 7.8 y 8.9 plants m-2) and the subplots to cultivars (‘Amarillo’, ‘Cacahuacintle’, ‘Jiquipilco’, ‘Z-60’, ‘Cóndor’ and ‘H-50’). The combined analysis of variance showed significant differences between years, densities and cultivars for all variables, except for light attenuation coefficient and intercepted radiation between years. The interactions were not significant, except in year × density in leaf area index and year × cultivar for grain yield. Among years, the cultivars average yield was higher in 2008 (1 133 g m-2), in 16.9% than 2009, due to the higher number of grains m-2 (2 826) and the radiation-use efficiency (0.79 g MJ-1). The best population densities were 7.8 and 8.9 plants m-2 (average of 1 081 and 1 096 g m-2, respectively) equivalent to 13.9% and 15.1% more than with 6.9 plants m-2. The above resulted from the best averages for these population densities in all variables under study. Among cultivars, ‘Jiquipilco’, ‘Amarillo’ and ‘Cóndor’ showed the highest average with 1 156, 1 076 and 1 047 g m-2.